The Victor Jara Case and the Long Struggle against Impunity in Chile - McSherry, J. Patrice (Social justice, 2014)
The article discusses the impunity of participants in the September 1973 coup in Chile, focusing on ongoing judicial case concerning the torture and murder of Chilean activist and singer-songwriter Víctor Jara at the start of the military dictatorship. Topics include coup leader General Augusto Pinochet; barriers to the transition to democracy and outstanding human rights violations cases; and the Chile Stadium massacre during which Jara was killed.